1999
DOI: 10.1016/s0006-3495(99)77111-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Association on the Structural Organization of Partially Folded Proteins: Inactivated Actin

Abstract: The propensity to associate or aggregate is one of the characteristic properties of many nonnative proteins. The aggregation of proteins is responsible for a number of human diseases and is a significant problem in biotechnology. Despite this, little is currently known about the effect of self-association on the structural properties and conformational stability of partially folded protein molecules. G-actin is shown to form equilibrium unfolding intermediate in the vicinity of 1.5 M guanidinium chloride (GdmC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 66 publications
3
51
0
Order By: Relevance
“…Aggregation or self-association is a characteristic property of partially folded (denatured) proteins (68 -72). It has been shown that in some cases the self-association induces additional structure and stability in the partially folded intermediates (73)(74)(75). Table I shows the far-UV CD parameters of ␣-synuclein determined at different protein concentrations and indicates that the spectrum is not affected by an ϳ170-fold increase in protein concentration, consistent with the lack of self-association up to at least 600 M. Fig.…”
Section: Effect Of Al 3ϩ On the Structural Properties And Aggregationmentioning
confidence: 52%
“…Aggregation or self-association is a characteristic property of partially folded (denatured) proteins (68 -72). It has been shown that in some cases the self-association induces additional structure and stability in the partially folded intermediates (73)(74)(75). Table I shows the far-UV CD parameters of ␣-synuclein determined at different protein concentrations and indicates that the spectrum is not affected by an ϳ170-fold increase in protein concentration, consistent with the lack of self-association up to at least 600 M. Fig.…”
Section: Effect Of Al 3ϩ On the Structural Properties And Aggregationmentioning
confidence: 52%
“…The structures adopted by antibodies at low pH are set apart from those of many other proteins [35][36][37] in that they are remarkably stable against unfolding and that they are oligomeric. In the original experiments performed with a complete IgG antibody, 13 it was not clear whether all domains of the antibody contribute to this structural state.…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate I 3 is formed when actin is unfolded in the presence of EDTA or as a result of heat denaturation, moderate denaturant concentration, by dialysis from high concentration of denaturant and spontaneously during storage . At moderate to high protein concentrations, irreversible aggregation of this species occurs (Bertazzon et al 1990;Kuznetsova et al 1999). The I 1 $ATP $$% !$$ I 2 C ATP equilibrium is rapidly established relative to the other steps (Kinosian et al 1993), and based on this assumption our stopped-flow fluorescence study has verified the reaction scheme and calculated the kinetic parameters (Altschuler et al 2005).…”
Section: The Folding and Unfolding Pathways Of Actinmentioning
confidence: 99%